Introductory Experiential Learning in IPE Teams: Changes in Team Collaboration and Cultural Attitudes and Beliefs - Farris, Karen B.; Bavireddy, Vinoothana; Bishop, Thomas; Marshall, Vincent D.; Anderson, Olivia (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2023)
Background: An introductory, longitudinal, authentic experiential IPE opportunity named LIFE was delivered. The objectives were to 1) compare attitudes, including cultural attitudes and beliefs, and team behaviours of learners over time, and 2) assess association between participation in LIFE and changes in team attitudes and performance.